VERBIALIZATION OF THE CONCEPT “HEART” IN ENGLISH AND UZBEK PARAMIOLOGICAL TEXTS (Ustozlar uchun, 2026)
This article explores the verbalization of the concept “heart” within English and Uzbek paramiological texts, analyzing both linguistic and cultural dimensions. The heart, as a metaphorical and symbolic entity, plays a central role in emotional, moral, and spiritual expressions in both languages. Through comparative semantic and pragmatic analysis, the study reveals how the heart is conceptualized and linguistically encoded, highlighting cultural-specific features and shared human experiences. The paper further investigates the usage of heart-related verbs, idiomatic expressions, and metaphorical structures, providing insights into the interaction between language, culture, and cognition in both English and Uzbek paramiologies.